Calendar Mysteries: June Jam - Book 6 - Roy, Ron 1940-; Gurney, John Steven 1962- (New York : Random House Children's Books, 2011)
As a Father's Day gift to the twins' Dad, Bradley, Brian, and their cousins Lucy and Nate try to identify and stop whatever creature is biting fruits and vegetables in the garden.
"A Stepping Stone Book."
Keywords: Gardens -- Fiction; Pests -- Fiction; Father's Day -- Fiction; Twins -- Fiction; Siblings -- Fiction; Cousins -- Fiction; Fiction